الحياة الاقتصادية والاجتماعية في منطقة الزواوة إلى ما قبل نهاية الحكم العثماني - - غضبان رميصاء (جامعة محمد بوضياف بالمسيلة)
My study is about the economic and social history of one the contry's regions, kabylie or Zouaoua. Laddressed and studied this topic through a group of local and foreign sources and references in an attempt to understand the economic pattern in the region, as well as the customs and traditions, and the extent to which the region's inhabitants to the peculiarities of their lives, as well as the customs and traditions, contributed to the cohesion of Zouaoua society تندرج دراستي حول التاريخ الإقتصاديوالإجتماعي لإحدى مناطق الوطن المتمثلة في منطقة القبائل أو زواوة وقد طرقت هذا الموضوع ودرسته من خلال مجموعة من المصادر والمراجع المحلية والأجنبية في محاولة للتعرف على النمط الإقتصادي في المنطقة وكذا العادات والتقاليد وإلى أي مدى ساهمت مقومات الإقتصادية المحلية للمنطقة وتأقلم سكان المنطقة بخصوصيات معيشتهم وكذلك العادات والتقاليد في تماسك المجتمع الزواوي.